2009
DOI: 10.4207/pa.2009.art33
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee (Pan troglodytes verus) Behavioral Responses to Stresses Associated with Living in a Savannah-Mosaic Environment: Implications for Hominin Adaptations to Open Habitats

Abstract: Anthropologists have long been interested in the behavioral ecology of nonhuman primates living in savannas given what we know of early hominin environments. As expected, chimpanzees in the Fongoli community in southeastern Sénégal show a unique suite of behavioral adaptations to stresses associated with their savanna habitat. While Fongoli chimpanzees are species-typical in certain regards, such as including ripe fruit in the diet during all months of the year, they also adjust their behavior to the particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
193
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(195 citation statements)
references
References 41 publications
(35 reference statements)
2
193
0
Order By: Relevance
“…Testing fecal samples from just two collection sites yielded a number of unexpected results. First, we found that the 67 Issa Valley chimpanzees all shared the same home range, indicating a community size much larger than that of other known savanna chimpanzees (4,34,46). Second, we discovered SIVcpz infection among these apes, indicating that there was, in fact, a second area of SIVcpz endemicity in Tanzania.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Testing fecal samples from just two collection sites yielded a number of unexpected results. First, we found that the 67 Issa Valley chimpanzees all shared the same home range, indicating a community size much larger than that of other known savanna chimpanzees (4,34,46). Second, we discovered SIVcpz infection among these apes, indicating that there was, in fact, a second area of SIVcpz endemicity in Tanzania.…”
Section: Discussionmentioning
confidence: 76%
“…The finding of 67 individuals within the Issa Valley study area, 64 of whom were interconnected by joint nesting episodes or diurnal associations, was surprising. Other known savanna chimpanzee communities are either much smaller (28 to 35 individuals) (4,34) or from sites with appreciably greater population densities (0.2 to 0.7/km 2 ) (14,46). The significance of such a large community (a minimum of 67 individuals) living at such a low density (less than 0.14 individual/km 2 ) is that the implied home range is enormous, i.e., greater than 478 km 2 , which is nearly twice the size of the largest similarly estimated home range published to date (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In semiarid regions, precipitation primarily determines water availability (15). Today, water availability shapes primate behaviors through its influence on vegetation and resource distributions (4,61). For example, regions with MAP <700 mm do not support chimpanzee populations (62).…”
Section: Interpretations and Discussionmentioning
confidence: 99%
“…However, they enter surface water in certain circumstances: at Fongoli, they immerse themselves in temporary rain-filled pools at the beginning of the rainy season, when it is still hot and humid; there they rest, groom and play (Pruetz & Bertolani 2009). Thus, water becomes a thermoregulatory device, even when potentially risky.…”
Section: (B) Dietmentioning
confidence: 99%